Product Quality Control in Reduced Dimension Spaces - Clarke-Pringle, Lee Tracy (My University, 1999)
In the first part of the thesis, control of the full molecular weight distribution (MWD) in a semi-batch polymerization reactor is considered. A new batch-to-batch optimization methodology for producing a desired MWD using an approximate fundamental model is presented. The optimization approach is also extended for use as an on-line control method by incorporating a multivariable statistical process control (MSPC) monitoring scheme. The combined MSPC/batch-to-batch optimizer is demonstrated on a simulated semi-batch polystyrene reactor and is shown to be very effective in reacting to large process upsets. Despite significant process/model mismatch, the batch-to-batch optimizer is able to adjust the process and produce the desired MWD within several batches following a process upset. In the remainder of the thesis, dimensionality issues in product quality control are addressed. First, indirect control of the full MWD by directly controlling only the average of the distribution is illustrated. It is shown that the choice of manipulated variables has an important impact on the controller performance when the full MWD is considered, and controlling a single average chain length sometimes causes the MWD to degrade. A simple analysis tool, called the Disturbance Inflation Factor (DIF), is introduced to evaluate which controlled and manipulated variables result in the best overall control of the full MWD. It is shown that with prudent choices of manipulated and controlled variables, simple single variable control can provide significant improvements in the full MWD. Controlling new linear combinations of the original inputs and outputs is also shown to be a feasible option for minimizing the overall effect of the disturbances. Finally, the thesis concludes with a critical review and unification of existing methods for Reduced Dimension Control. It was found that due to the different industries from which the applications originate, there is little or no comparison of similar approaches, thus there is the need for a unification. (Abstract shortened by UMI.)
Keywords: Chemical Engineering; Chemical Engineering